The portrait of a teacher from the innovative higher education – students’ viewpoint; SHS Web of Conferences; Vol. 28 : Research Paradigms Transformation in Social Sciences (RPTSS 2015) - Mertins K. V. Kseniya Viktorovna; Ivanova V. S. Veronika Sergeevna; Kurkan N. V. Nataliya Vladimirovna; Zatonov I. A. Ivan Andreevich (2016, 2016)
Title screen